Membrane bioreactor processes : principle and application - Yoon, Seong-Hoon (Advances in water and wastewater transport and treatment, 2015)
"Preface Membrane technology has been rapidly developed in recent decades to meet various needs from various industries. I was lucky to be a graduate student when the theories on membrane filtration were being matured and countless new technologies emerged in the 1990s. Membrane bioreactor (MBR) technology was one of the emerging technologies at the time, and it is now one of the most successful membrane processes of all time along with reverse osmosis (RO). I started MBR research in graduate school and continued it throughout my carrier as a research engineer of the LG group and Nalco. I have to admit I have been greatly indebted to everyone who contributed to the advance of membrane technology. Although the knowledge base of MBR has been expanded in the last two decades, the gaps between the leading edge academic research and the practical know-how obtained from the field have also been widened. Hoping to fill the gap, I started to share my experience in the academics and the field through my blog (http://www.onlinembr.info) since 2011. This open-source knowledge sharing was a great success, having more than 200 unique visitors a day globally, almost equally distributed among the Americas, Europe, and Asia. The questions and comments I received were a great source of new information and inspiration. With numerous encouragements from the audiences, I took courage to author this book. The contents in the blog were thoroughly reviewed and modified with additional fillers to make the contents more rigorous and complete. This book is written with an emphasis on the principles behind the scene instead of simply introducing the way MBR works. Chapters 1 and 2 are about the fundamentals of membrane filtration relevant to MBR. Chapter 2 is specifically about the"--